2017
DOI: 10.4317/medoral.22013
|View full text |Cite
|
Sign up to set email alerts
|

The assessment of surgical and non-surgical treatment of stage II medication-related osteonecrosis of the jaw

Abstract: BackgroundNon-surgical treatment has generally been recommended for stage II medication-related osteonecrosis of the jaw (MRONJ) in preference to surgery. However, non-surgical treatment is not empirically effective. The aim of this study was to evaluate whether surgical or non-surgical treatment leads to better outcomes for stage II MRONJ.Material and MethodsIn this retrospective study, surgery was performed in a total of 28 patients while 24 patients underwent non-surgical treatment. The outcomes of both tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 28 publications
(24 reference statements)
0
15
0
6
Order By: Relevance
“…In the past, the surgical treatments were reserved only for advanced stages of BRONJ; the Italian Society of Oral and Maxillofacial Surgery (SICMF) and the Italian Society of Oral Pathology and Medicine (SIPMO) in 2012 recommended conservative surgery in lesions belonging to stages I and II, as defined by both societies, that can provide resolution of acute infection and offers long-term of well-being for patients [ 10 , 11 , 13 – 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the past, the surgical treatments were reserved only for advanced stages of BRONJ; the Italian Society of Oral and Maxillofacial Surgery (SICMF) and the Italian Society of Oral Pathology and Medicine (SIPMO) in 2012 recommended conservative surgery in lesions belonging to stages I and II, as defined by both societies, that can provide resolution of acute infection and offers long-term of well-being for patients [ 10 , 11 , 13 – 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned above, surgical treatment is close to the most standard treatment in the management of MRONJ. Its effectiveness has already been widely proven in Stages 2 and 3 [ 59 , 60 , 61 , 62 , 63 ]. Recently, a prospective cohort study has reported that it is also useful in early stages such as Stage 1.…”
Section: Various Therapeutic Methods For Mronjmentioning
confidence: 99%
“…Terapias Teciduais (Mauceri et al, 2018;Inchingolo et al, 2017;Mourão et al, 2020;Calvani et al, 2018;Lemound et al, 2018;Coviello et al, 2012;Park et al, 2017;Jung et al, 2017;Aljohani et al, 2019;Mozzati et al, 2012;Curi et al, 2011;Rotaru et al, 2015) 254 248 80 240 66,85 anos Terapias Adjuvantes (Freiberger et al, 2012;Ristow et al, 2017;Agrillo et al, 2012;Atalay et al, 2011;Ripamonti et al, 2011;Giudice et al, 2018;Kwon et al, 2012;Laimer et al, 2017;Bedogni et al, 2011;Stübinger et al, 2009;Voss et al, 2017) 332 302 110 192 66,45 anos Tratamentos Cirúrgicos (Favia et al, 2018;Voss et al, 2012;El-Rabbany et al, 2019;Lopes et al, 2015;Kim et al, 2017;Hoefert et al, 2017;Eguchi et al, 2017;Ruggiero & Kohn, 2015;Favia et al, 2016;Stockmann et al, 2010;Rugani et al, 2015;Hallmer et al, 2018;Reich et al, 2015;Aljohani et al, 2018 Observou-se que o maxilar mais acometido pela ONMIM é a mandíbula. As lesões estavam presentes na maxila em 725 pacientes, na mandíbula em 1817 pacientes e em ambos os maxilares em 98 pacientes (Giudice et al, 2018;…”
Section: Nº Homensunclassified
“…As lesões estavam presentes na maxila em 725 pacientes, na mandíbula em 1817 pacientes e em ambos os maxilares em 98 pacientes (Giudice et al, 2018;Favia et al, 2016;Rotaru et al, 2015;Karasneh et al, 2016;Thumbigere-Math et al, 2009;Ripamonti et al, 2011;Kwon et al, 2012;Laimer et al, 2017;Bedogni et al, 2011;Stockmann et al, 2010;Hallmer et al, 2018;Reich et al 2015;Mauceri et al, 2018;Mourão et al, 2020;Calvani et al, 2018;Lemound et al, 2018;Coviello et al, 2012;Park et al, 2017;Ikeda et al, 2015;Nisi et al, 2018;Lee et al, 2014;Moretti et al, 2011;Fortuna et al, 2012;Ristow et al, 2017;Agrillo et al, 2012;Atalay et al, 2011;Favia et al, 2018;Voss et al, 2012;El-Rabbany et al, 2019;Lopes et al, 2015;Kim et al, 2017;Hoefert et al, 2017;Eguchi et al, 2017;Ruggiero & Kohn, 2015;Owosho et al, 2016;Lerman et al, 2013;Coropciuc et al, 2017;Stübinger et al, 2009;Voss et al, 2017;Aljohani et al, 2018;Aljohani et al, 2019;Mozzati...…”
Section: Nº Homensmentioning
confidence: 99%
See 1 more Smart Citation